Length-weight relationship of Penaeus indicus and Penaeus merguiensis in the Langsa mangrove area, Aceh Province. Issue 1 (November 2021) - Maulida, S; Iqbal, T H; Firmanhadi, F; Nur, F M; Fadli, N; Ulfah, M; Suman, A; Damora, A
Abstract: The two Penaeid shrimps Penaeus indicus and Penaeus merguiensis are the most common commercial species found in the Langsa mangrove forest. The growth pattern of these two Penaeid shrimps are strongly influenced by environmental factors such as temperature, pH, dissolved oxygen (DO), salinity, availability of food and predators, which ultimately determines the abundance and catch of commercial adult shrimps obtained. The present study aims to investigate the length-weight relationship of P. indicus and P. merguiensis in the Langsa mangrove forest, Aceh Province. The sampling was conducted in November 2018 with the stratified random sampling method. A total of 124 shrimps consisted of 92 samples P. indicus and 32 samples P. merguiensis . The results showed that growth pattern of two Penaeid shrimps was categorized as negative allometric. The highest b value is shown in P. merguiensis with b value of 2.87 while P. indicus 2.55. The value of the relative weight condition factor (Wr) of the two shrimps indicates a value of >100. It is concluded that the waters of the mangrove forest in Langsa City are still able to support the survival of P. indicus and P. merguiensis .